Evaluation Of Road Channel As A Drainage Function For Agricultural Land Remediation - Noor Salim (International Applied Science, 2022)
The Ring Road section on the West Ring Road - Madiun City is an alternative road which connecting the outside of Madiun city to the Madiun city. That road is a road with both side of it is a rice field. As a road, it must be clean from puddles when it rains. So that it does not cause traffic problems in the form of traffic disorder. Bad road channels have an impact on flooding due to rain and make the level of road service in the area decrease. On the other hand, the road channel in the area can also be used as a channel for removing pollutants from agricultural land in the rice fields. So that the process of remediation of agricultural land can run smoothly. This highway channel is highly influenced by the local climate, especially the existing of rainfall. Based on that, there is a need for Adequacy Evaluation of the Roadside of the Rice Fields as a drainage function in Agricultural Land Remediation, with a case study on the Ring Road channel in the West Ring Road - Madiun City. From the results of the analysis in this study, it was found that there are two size of Highway Channel Size on the Ring Road in the West Ring Road - Madiun City and both of them are in good conditions. Channel A1 with size b = 0.71 m, H = 0.36 m and h = 0.11 m. Channel A2 with size b = 0.75 m, H = 0.38 m and h = 0.11 m. The results of the design flood rainfall calculation show that there are variations in values that do not much differ in the return period of 2 years to 25 years and can be used as a reference in the management of small irrigation, drainage systems, and small-scale weir buildings, including calculation of road channels on the Ring Road in the Ring Road Section West-Madiun City. From the analysis, it was found that the road channels on the West Ring Road of Madiun City are still good and adequate. From the analysis of the square and trapezoidal dimensions, it is found that the channel discharge is > the planned discharge, so the dimensions of the channel can accommodate the flood discharge that will occur in a period of 25 years, both as a function of road drainage and as drainage in Agricultural Land Remediation in the rice fields along the road. It is suggested that the need for channel maintenance on the road sections on the Ring Road in the West Ring Road - Madiun City and for further studies regarding other road infrastructure and facilities to support road service levels and as a function for agricultural land drainage